2013
DOI: 10.1002/mds.25495
|View full text |Cite
|
Sign up to set email alerts
|

Changes in endolysosomal enzyme activities in cerebrospinal fluid of patients with Parkinson's disease

Abstract: Parkinson's disease (PD) is characterized neuropathologically by the cytoplasmic accumulation of misfolded α-synuclein in specific brain regions. The endolysosomal pathway appears to be involved in α-synuclein degradation and, thus, may be relevant to PD pathogenesis. This assumption is further strengthened by the association between PD and mutations in the gene encoding for the lysosomal hydrolase glucocerebrosidase. The objective of the present study was to determine whether endolysosomal enzyme activities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 48 publications
3
81
0
Order By: Relevance
“…Emerging data on the detection of elevated levels of oligomeric and phosphorylated forms of CSF α-syn, along with changes in the levels of CSF lysosomal enzymes in PD indicates that these proteins could be useful biomarkers of pathology (Park, et al, 2011,Parnetti, et al, 2014a,Parnetti, et al, 2014b,Tokuda, et al, 2010,van Dijk, et al, 2013,Wang, et al, 2012). Measurement of other CSF proteins may yield additional biomarkers for PD, including proteins present in both the CSF and the cortical proteomes identified by proteomic analysis (Pan, et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data on the detection of elevated levels of oligomeric and phosphorylated forms of CSF α-syn, along with changes in the levels of CSF lysosomal enzymes in PD indicates that these proteins could be useful biomarkers of pathology (Park, et al, 2011,Parnetti, et al, 2014a,Parnetti, et al, 2014b,Tokuda, et al, 2010,van Dijk, et al, 2013,Wang, et al, 2012). Measurement of other CSF proteins may yield additional biomarkers for PD, including proteins present in both the CSF and the cortical proteomes identified by proteomic analysis (Pan, et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the combination of GCase activity, oligomeric/total α-Syn ratio and age discriminates best PD from neurological controls 89. However, in a Dutch cohort of de novo PD patients and healthy controls, there was a trend towards a reduction in CSF GCase activity 90. The usefulness of GCase as a potential biomarker in parkinsonian conditions needs to be evaluated in future studies that include additional neurodegenerative groups to PD.…”
Section: Other Candidate Markersmentioning
confidence: 99%
“…Studies measuring CSF levels of lysosomal hydrolases (involved in the α-Syn degradation) found decreased (Balducci et al, 2007), normal (van Dijk et al, 2013b), or increased (Parnetti et al, 2014a) β-hexosaminidase, increased cathepsin E (van Dijk et al, 2013b), decreased α-mannosidase (Balducci et al, 2007), decreased (Balducci et al, 2007) or normal β-mannosidase (Mollenhauer et al, 2011; van Dijk et al, 2013b), decreased α-fucosidase (van Dijk et al, 2013b), β-glucocerebrosidase decreased (Balducci et al, 2007; Parnetti et al, 2014a) or normal (van Dijk et al, 2013b), β-galactosidase increased (van Dijk et al, 2013b) or normal (Balducci et al, 2007; Parnetti et al, 2014a), and cathepsin D normal (van Dijk et al, 2013b) in PD patients compared with controls.…”
Section: Proteins Involved In the Pathogenesis Of Parkinson's Diseasementioning
confidence: 99%